PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PEMBELAJARAN TIME TOKEN DALAM PENDIDIKAN PANCASILA DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low critical thinking skills of fifth-grade students at UPT SDN 008 Langgini. The purpose of this study is to improve the critical thinking skills of fifth-grade students at UPT SDN 008 Langgini by applying the Time Token learning model. This type of research is classroom action research (CAR). The research was conducted in 2 cycles, with each cycle consisting of two meetings. The subjects of this study were 16 fifth-grade students at UPT SDN 008 Langgini. The data collection techniques used in this study were observation, documentation, and tests. Based on the results of the study, it can be concluded that the students' critical thinking skills improved in each cycle, with the percentage results for cycle I meeting I at 44%, cycle I meeting II at 62%, cycle II meeting I at 75%, and cycle II meeting II at 87%. Thus, it can be concluded that the application of the Time Token learning model in Pancasila Education can improve the critical thinking skills of fifth-grade students at UPT SDN 008 Langgini. Further strategic steps are needed.